Assessing Racial/Ethnic Disparities in Treatment across Episodes of Mental Health Care. (16th July 2013) - Cook, Benjamin Lê; Zuvekas, Samuel H.; Carson, Nicholas; Wayne, Geoffrey Ferris; Vesper, Andrew; McGuire, Thomas G.
<x xml:space="preserve">Abstract</x> Objective To investigate disparities in mental health care episodes, aligning our analyses with decisions to start or drop treatment, and choices made during treatment. Study Design We analyzed whites, blacks, and Latinos with probable mental illness from Panels 9–13 of the Medical Expenditure Panel Survey, assessing disparities at the beginning, middle, and end of episodes of care (initiation, adequate care, having an episode with only psychotropic drug fills, intensity of care, the mixture of primary care provider (PCP) and specialist visits, use of acute psychiatric care, and termination). Findings Compared with whites, blacks and Latinos had less initiation and adequacy of care. Black and Latino episodes were shorter and had fewer psychotropic drug fills. Black episodes had a greater proportion of specialist visits and Latino episodes had a greater proportion of PCP visits. Blacks were more likely to have an episode with acute psychiatric care. Conclusions Disparities in adequate care were driven by initiation disparities, reinforcing the need for policies that improve access. Many episodes were characterized only by psychotropic drug fills, suggesting inadequate medication guidance. Blacks' higher rate of specialist use contradicts previous studies and deserves future investigation. Blacks' greater acute mental health care use raises concerns over monitoring of their treatment.